Pembentukan Portofolio Optimal Saham Perbankan Menggunakan Single Index Model Analisis Pada Saham LQ-45 Periode 2018-2019 - Mastur; Indra Suhendra (J-DBS: Journal of Darunnajah Business School, 2024)
Abstract The expectation of an investment risk and return is the relationship of an investor who is able to reduce risk by carrying out portfolio diversification. One of the analysis models between portfolio risk and return is using a single index model. Many stocks on the stock exchange make an investor confused in choosing good stocks for portfolio development. To that end, the Indonesia Stock Exchange has created a stock index that has very high liquidity, has a large market capitalization, good financial condition and fundamentals that are incorporated in the liguid 45 index (LQ-45). This study intends to determine which banking stocks can be included in the optimal portfolio, and ultimately determine the portion of the fund placement of each stock in the optimal portfolio. This study uses descriptive research and the approach used is a quantitative approach. The population of this study is banking stocks which are included in the LQ-45 during the 2018-2019 period. The data source comes from the internet, namely https://idx.co.id/. The results showed that from 5 banks there were 3 banks that formed an optimal portfolio composition with shares of BBCA 78.7%, BBRI 15.5% and BBNI 5.7%. Keywords: Portofolio optimal, single index model, perbankan, indexes LQ 45.